Paramedic perceptions of the feasibility and practicalities of prehospital clinical trials: a questionnaire survey. Issue 6 (19th March 2013) - Hargreaves, Kate; Goodacre, Steve; Mortimer, Peter
Abstract : Background: Clinical trials are required to strengthen the evidence base for prehospital care. This questionnaire study aimed to explore paramedics' perceptions of prehospital research and barriers to conducting prehospital clinical trials. Methods: A self-completed questionnaire was developed to explore paramedic perceptions and barriers to undertaking prehospital trials based upon a review of existing research and semistructured qualitative interviews with five paramedics. The questionnaire was distributed by 'research champions' to 300 paramedics at randomly selected ambulance stations in Yorkshire. Results: Responses were received from 96/300 participants (32%). Interest in clinical trials was reported, but barriers were recognised, including perceptions of poor knowledge and limited use of evidence, that conducting research is not a paramedics' responsibility, limited support for involvement in trials, concerns about the practicalities of randomisation and consent, and time pressures. No association was found between training route and perceived understanding of trials (p=0.263) or feeling that involvement in trials was a professional responsibility (p=0.838). Previous involvement in prehospital research was not associated with opinions on importance of an evidence base (p=0.934) or gaining consent (p=0.329). The number of years respondents had been practicing was not associated with opinions on personal experience versus scientific evidence (p=0.582) or willingness to receive training for clinical trials (p=0.111). However, the low response rate limited the power of the study to detect potential associations. Conclusions: Paramedics reported interest and understanding of research, but a number of practical and ethical barriers were recognised that need to be addressed if prehospital clinical trials are to increase.